Satisfaction With the Use of a Mobile Application: Adopsi Teknologi pada Aplikasi Mobile PLN - Lestariningsih, Nuri; Dewi, Citra Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of information technology has an impact on business growth in Indonesia. One example is PT PLN developing the PLN mobile application to facilitate customers in accessing the services provided. The purpose of this study is to determine the influence of Barriers (Resistance to change and Technological Complexity) and Facilitators (Technical Support, Compatibility, Performance Expectancy, and Easy of use) on Satisfaction with the use of a mobile application in the Mobile PLN app. The research method used in this study is a quantitative method by distributing questionnaires to users of the PLN mobile app. The results of the study indicate that resistance to change positively affects user satisfaction with the mobile PLN application, as users feel more satisfied when the application does not disrupt their routines. Conversely, technological complexity negatively affects user satisfaction; the higher the complexity, the lower the satisfaction. A stable and easy-to-use application increases satisfaction. Effective and responsive technical support also enhances user satisfaction. The application's compatibility with users' lifestyles has a significant impact; an application integrated with users' routines increases satisfaction. Fulfilled performance expectations, such as tangible benefits, efficiency, and productivity, also positively affect user satisfaction. Easy of use has a significant influence; an intuitive and user-friendly application increases overall user satisfaction.